2015
DOI: 10.1039/c4ob02284j
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free, efficient hydrazination of imidazo[1,2-a]pyridine with diethyl azodicarboxylate in neutral media

Abstract: The first example of metal-free regioselective hydrazination of imidazo[1,2-a]pyridine with diethyl azodicarboxylate was accomplished. This procedure is chemically appealing due to the high degree of functional group tolerance and efficiency in expanding molecule diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…As part of our continued efforts to develop C‐C and C‐N bond formation reactions, particularly with imidazopyridines,, , we investigated the use of a Mannich‐like reaction for C‐3 aminomethylation of imidazo[1,2‐ a ]pyridines. Previously, the Mannich reaction has served as a tool to functionalize electron dense heterocycles and phenols using formaldehyde as a methylene source via acid catalyzed alkyl‐amination .…”
Section: Introductionmentioning
confidence: 99%
“…As part of our continued efforts to develop C‐C and C‐N bond formation reactions, particularly with imidazopyridines,, , we investigated the use of a Mannich‐like reaction for C‐3 aminomethylation of imidazo[1,2‐ a ]pyridines. Previously, the Mannich reaction has served as a tool to functionalize electron dense heterocycles and phenols using formaldehyde as a methylene source via acid catalyzed alkyl‐amination .…”
Section: Introductionmentioning
confidence: 99%
“…9 More recently, the hydrazination of such compounds with diethyl azodicarboxylate in the absence of metal catalysts was described (Scheme 1c). 10 As well, the regioselective C-3 sulfenylation of imidazo[1,2-a]pyridines has been achieved with various sulfenylating reagents, 11 including disulfides, thiophenols, 35 sodium sulfinates and sulfonyl hydrazides (Scheme 1d). In addition, methylthiolation using a DMSO-POCl 3 complex has been demonstrated (Scheme 1e).…”
mentioning
confidence: 99%
“…5 provided 3aa in 87% yield (Table 1, entry 6), whereas further decreases in the charge of NH 2 CN resulted in significant decreases in the yields (Table 1, entries 3-5). Accordingly, various amines and other bases were also evaluated, but none had a positive impact on the outcome of the reaction (see Supporting 10 Information). These results indicated that NH 2 CN is an important mediator in this transformation.…”
mentioning
confidence: 99%
See 2 more Smart Citations